Road Assessment: Analyzing Geometric Standards Compliance With The Power Of Open-Source Google Earth - A Case Study Of Waecicu Road, West Manggarai - Tommy Timur Kurniawan; Mulia Pamadi (Fakultas Teknik Sipil dan Perencanaan, 2023)
This study conducted a case study on Waecicu Road in NTT to evaluate its compliance with the Indonesian Road Geometric Design Guidelines 2021. It aims to revolutionize the process of road assessment by utilizing the power of open-source Google Earth. The study found that Google Earth's features, such as satellite imagery, 3D modeling, and measurement tools, provide a powerful and cost-effective means to assess road geometry, including lane width, slope, and curvature. Using Google Earth, road engineers and planners can quickly identify problem areas and take necessary measures to improve road safety and compliance with standards. The study's findings could contribute to developing more effective and efficient road assessment techniques, particularly in areas with limited resources and infrastructure.